2015
DOI: 10.3390/v7082832
|View full text |Cite
|
Sign up to set email alerts
|

Replication and Inhibitors of Enteroviruses and Parechoviruses

Abstract: The Enterovirus (EV) and Parechovirus genera of the picornavirus family include many important human pathogens, including poliovirus, rhinovirus, EV-A71, EV-D68, and human parechoviruses (HPeV). They cause a wide variety of diseases, ranging from a simple common cold to life-threatening diseases such as encephalitis and myocarditis. At the moment, no antiviral therapy is available against these viruses and it is not feasible to develop vaccines against all EVs and HPeVs due to the great number of serotypes. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
63
0
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(70 citation statements)
references
References 215 publications
0
63
0
7
Order By: Relevance
“…than any virus lacking this mutation. Picornaviruses replicate their RNA on reorganized cellular membrane structures designated “replication organelles.” The virus-induced lipid composition of these regions differs significantly from normal cellular membranes (Belov, 2014; van der Linden et al, 2015). For enteroviruses, including the RV, non-structural proteins 2BC and 3A display hydrophobic domains that are somehow involved in this process of internal membrane rearrangement, presumably through interactions with a number of host cell proteins.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…than any virus lacking this mutation. Picornaviruses replicate their RNA on reorganized cellular membrane structures designated “replication organelles.” The virus-induced lipid composition of these regions differs significantly from normal cellular membranes (Belov, 2014; van der Linden et al, 2015). For enteroviruses, including the RV, non-structural proteins 2BC and 3A display hydrophobic domains that are somehow involved in this process of internal membrane rearrangement, presumably through interactions with a number of host cell proteins.…”
Section: Discussionmentioning
confidence: 95%
“…For enteroviruses, including the RV, non-structural proteins 2BC and 3A display hydrophobic domains that are somehow involved in this process of internal membrane rearrangement, presumably through interactions with a number of host cell proteins. These include Golgi-specific brefeldin A-resistance guanine nucleotide exchange factor 1 (GBF1), phosphatidylinositol 4-kinase type III β (PI4KIIIβ) and the Golgi adaptor protein acyl-CoA-binding domain-containing protein 3 (ACBD3) (Wessels et al, 2006; van der Linden et al, 2015). It has been demonstrated that transient expression of an A16 3A protein by transfection, can lead to disruption of the Golgi structure and inhibition of cellular protein secretion (Mousnier et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Several compounds have progressed into clinical trials, but none of them has been formally approved by the FDA due to limited efficacy or safety concerns (14)(15)(16)(17). Combining antiviral agents with additive or synergistic antiviral effects is a proven strategy to increase antiviral potency and reduce potential toxicity and adverse effects.…”
mentioning
confidence: 99%
“…Thus, there is rationale to continue to identify and characterize new antipolioviral agents for ultimate development of therapeutic drugs against PV infections. 17 …”
mentioning
confidence: 99%